Aberrant lipid profiles and lymphocyte counts in systemic sclerosis population, reassessing predictive value for concurrent cardiovascular diseases - Guo, Ronghong; Gao, Jinfang; Yang, Yanli; Xu, Ke (Frontiers in Immunology, 2025)
ObjectiveTo investigate alterations in blood lipid profiles and T cell subsets among systemic sclerosis (SSc) patients, and to assess their potential utility in predicting cardiovascular disease (CVD) risk.Methods105 SSc patients and 80 age- and sex-matched healthy controls (HCs) were enrolled. Flow cytometry was employed to quantify T cell subsets. Multivariate logistic regression analysis investigated the association between blood lipid profile, T cell subsets, SSc occurrence, and CVD risk. Additionally, a prediction model was developed to assess the potential predictive value of CVD risk.ResultsIn the SSc patients, low-density lipoprotein cholesterol (LDL-C) (OR = 3.212, 95%CI = 1.132-9.113, p= 0.028), ESR (OR = 1.218, 95%CI = 1.086-1.367, p= 0.001), CRP (OR = 2.156, 95% CI = 1.393-3.338, p = 0.001), T helper (Th)cells (OR = 1.004, 95% CI = 1.001-1.008, p = 0.034) were positively correlated with the risk of SSc. Further studies found that absolute increases in Th cells in SSc patients were positively associated with the risk of CVD (OR=1.002, 95%CI=1.001-1.005, p =0.011) and were independent predictors of CVD risk in SSc. When Th cells exceeded 866.53 cells/μL, the risk of CVD in SSc patients was greatly increased (p<0.001).ConclusionAltered lipid profiles and dysregulated Th cell expression in SSc patients, with a significant elevation of Th cells specifically noted in SSc-CVD patients, suggesting that Th cells may serve as a potential predictive biomarker for CVD in SSc patients, thereby aiding in early diagnosis. The underlying mechanism of this association requires further investigation.